A comparative analysis about natural user interface technologies - Ferreira, Adriano Oliveira Lima; Xavier, Krishna Ferreira; Peroba, Jamir Alves; Cardoso, Rafael Cunha; Costa, Vinícius Kruger da; Rodrigues, Andréia Sias; Machado, Marcelo Bender; Tavares, Tatiana Aires (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2017: Anais Estendidos do XXIII Simpósio Brasileiro de Sistemas Multimídia e Web, 2017)
This paper contains a comparison between some market consolidated devices which use a Human–Computer Interface through the user’s natural actions (Natural User Interface), such as gestures and speech. The goal is to identify their main functionalities, so that they are used later on to define the requirements needed for developing projects with similar characteristics. The idea is to also gather this information so that it is possible to compare these marketed devices to the developing project called Interface Óculos Mouse (IOM). IOM uses a Natural Interface to allow physically challenged users to control the cursor through head movements. This study will verify which features still need to be developed in order to make the IOM prototype an industrialized product.